The Effect of Work Discipline and Motivation on Employee Performance at PT. Karuna Intermedia - Iman Syatoto (Universitas Negeri Makassar, 2019)
Human Resources (HR) is the most vital resource that determines the success of a company. The purpose of this study was to determine the effect of discipline and work discipline on employee work performance. The method used is descriptive method with an associative approach. The sampling technique used was proportional random sampling using the method of saturated sampling technique with a sample of 40 respondents. The analysis tool uses validity test, reliability test, classic assumption test, regression test, correlation coefficient test, coefficient of determination test and hypothesis test. The result of this study is that work discipline has a positive and significant effect on employee performance by 49.7%. Hypothesis testing is obtained tcount> ttable or (6.131> 2.024), so that H0 is rejected and H1 is accepted meaning that there is a positive and significant influence between discipline on employee work performance. discipline has a positive and significant effect on employee performance by 45.4%. Hypothesis testing is obtained tcount> ttable or (5.625> 2.024) so that H0 is rejected and H2 is accepted, meaning that there is a positive and significant influence between discipline on employee work performance. A simultaneous test of work discipline and discipline has a positive and significant effect on employee performance with a contribution of 58.2%, while the remaining 41.8% is influenced by other factors. Hypothesis testing obtained the value of Fcount> Ftable or (25.798> 2.860) g thus Ho is rejected and H3 is accepted. This means that there is a positive and significant effect simultaneously between discipline and work discipline on employee work performance.